Recent advances in polar low research: current knowledge, challenges and future perspectives - Marta Moreno-Ibáñez (Taylor & Francis Group, 2021)
Polar lows (PLs) are high-latitude intense maritime mesoscale weather systems that develop over open water near the sea ice margin or near snow-covered continents during cold air outbreaks. PLs pose a threat to coastal and island communities, transportation and offshore drilling platforms. PLs mainly develop during the cold season and their frequency exhibits a large interannual variability. Observations from polar-orbiting satellites are the main source of observational data to study PLs since conventional observations are sparse and unevenly distributed in high latitudes. PL forecasting has long remained a challenge due to the small size and short lifetime of these systems. Nevertheless, the representation of PLs in numerical models has significantly improved with the advent of high-resolution atmospheric models. Several studies have shown that baroclinic instability and convection play an important role in the development of PLs, but a thorough understanding of the physical mechanisms involved in the formation and intensification of PLs is yet to be developed. The relevant role of surface sensible heat flux and latent heat release in PL development has often been highlighted. The diabatic fluxes from the oceanic surface and associated with PLs can cause a decrease in the sea surface temperature (SST), whereas the strong wind speeds can lead to upper-ocean mixing in regions where an ocean temperature inversion is present. It is expected that global warming associated with anthropogenic climate changes may lead to an increase in the static stability of the atmosphere, thus affecting the climatology of PLs. In the North Atlantic the regions of PL activity will shift northwards as seasonal sea-ice margins migrate towards higher latitudes areas, and the frequency of PLs will decrease. Although our knowledge about PLs has significantly increased during the last decades, the are still many unanswered questions. Among the most pressing issues in PL research are the need to determine the objective criteria that define PLs and to devise an international intercomparison project of PL detection and tracking.